1998
DOI: 10.1007/bf02303642
|View full text |Cite
|
Sign up to set email alerts
|

Surgery versus surgery and postoperative radiotherapy in squamous cell carcinoma of the buccal mucosa: A comparative study

Abstract: Postoperative radiotherapy was effective in decreasing locoregional failure in patients with close surgical margins, tumor thicker than 10 mm, high-grade tumors, positive node, and bone invasion. The effect of interval between surgery and postoperative radiotherapy on local failure was margin-dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
48
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 19 publications
2
48
2
2
Order By: Relevance
“…Nair et al 24 from India reported that 109 patients of 238 who received radiotherapy alone had persistent or locoregional recurrent disease. Also from 15 reported on 115 patients treated by surgery alone compared with 61 patients treated by surgery plus postoperative radiotherapy. Actuarial 3-year locoregional control rates for advanced-stage disease in these two groups were 11% and 48%, respectively, in favor of surgery plus postoperative radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nair et al 24 from India reported that 109 patients of 238 who received radiotherapy alone had persistent or locoregional recurrent disease. Also from 15 reported on 115 patients treated by surgery alone compared with 61 patients treated by surgery plus postoperative radiotherapy. Actuarial 3-year locoregional control rates for advanced-stage disease in these two groups were 11% and 48%, respectively, in favor of surgery plus postoperative radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This falls within the 29% to 100% incidence reported in the literature. 15,21,23 A previous report from Taiwan on 57 patients concluded that postoperative radiotherapy was effective in decreasing locoregional failure in patients with close surgical margins, tumor thickness greater than 10 mm, high-grade tumors, and positive node and bone invasion. 13 Of the patients in this study, the S group and S + RT group had similar treatment outcomes in both early and advanced stages despite the fact that 20 of the 58 patients who had S + RT had positive or close surgical margins, whereas no patient in the S group had positive margins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dixit et al beobachteten eine erhöhte Lokalrezidivrate bei einer postoperativen Wartezeit von > 30 Tagen und knappen Resektionskanten [9]. Nach Parsons et al [23] lag der kritische Grenzwert bei positiven Resektionskanten bei 45 Tagen.…”
Section: Diskussionunclassified